Faktor Motivasi dan Faktor Higiene Pegawai Negeri Sipil di Indonesia - Mario Emilzoli; Syafril Ramadhon (Jurnal Ilmiah Administrasi Pemerintahan Daerah, 2026)
This study aims to identify the factors influencing the motivation of civil servants in Indonesia by adapting Herzberg’s Motivation-Hygiene Theory. A quantitative survey approach was employed. The research instrument was a rating scale designed to assess respondents’ perceptions of motivation and hygiene factors using a four-point Likert scale. The respondents were civil servants working in various central and regional government institutions across Indonesia. Data were collected online through a Google Forms questionnaire from May to August 2023, yielding 303 valid responses. The findings indicate that the main factors that internally motivate civil servants in Indonesia are recognition, responsibility, opportunities for growth, and achievement. Meanwhile, hygiene factors that may reduce motivation because they are perceived as not yet meeting expectations include policies and administrative systems in government institutions, salary, supervisory capability, working conditions, and employment status.